2015
DOI: 10.1186/s12882-015-0052-2
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacist based intervention to improve the care of patients with CKD: a pragmatic, randomized, controlled trial

Abstract: BackgroundPrimary care providers do not routinely follow guidelines for the care of patients with chronic kidney disease (CKD). Multidisciplinary efforts may improve care for patients with chronic disease. Pharmacist based interventions have effectively improved management of hypertension. We performed a pragmatic, randomized, controlled trial to evaluate the effect of a pharmacist based quality improvement program on 1) outcomes for patients with CKD and 2) adherence to CKD guidelines in the primary care sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 31 publications
2
83
0
2
Order By: Relevance
“…Although adherence to dosing did not differ between the morning and evening groups in the current study, a previous study assessed electronically compiled dosing histories to investigate adherence to prescribed antihypertensive medications in 4783 patients and found that patients were more likely to take their medications as prescribed in the morning than in the evening (26). Previous studies have demonstrated that pharmacist-based interventions can improve adherence in both the CKD patient population and in primary care (14–21,27). The results of the current study further support the notion that pharmacist-based interventions can improve adherence in chronic patient disease populations, but as identified in previous clinical studies, further research must be conducted to evaluate the impact of adherence on long-term clinical outcomes (21,27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although adherence to dosing did not differ between the morning and evening groups in the current study, a previous study assessed electronically compiled dosing histories to investigate adherence to prescribed antihypertensive medications in 4783 patients and found that patients were more likely to take their medications as prescribed in the morning than in the evening (26). Previous studies have demonstrated that pharmacist-based interventions can improve adherence in both the CKD patient population and in primary care (14–21,27). The results of the current study further support the notion that pharmacist-based interventions can improve adherence in chronic patient disease populations, but as identified in previous clinical studies, further research must be conducted to evaluate the impact of adherence on long-term clinical outcomes (21,27).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that pharmacist-based interventions can improve adherence in both the CKD patient population and in primary care (14–21,27). The results of the current study further support the notion that pharmacist-based interventions can improve adherence in chronic patient disease populations, but as identified in previous clinical studies, further research must be conducted to evaluate the impact of adherence on long-term clinical outcomes (21,27). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of studies bridging nephrology and primary care include trials of CKD care coordination with patient navigators 30 and strategies to implement guidelineconcordant CKD care with electronic checklists, 31 primary care practice facilitation, 32 and pharmacist-led interventions. 33 Third, pragmatic trials offer an opportunity to examine clinical questions that have been identified by diverse stakeholders, including patients, caregivers, and providers, as high-priority CKD research areas (Box 1). 34,35 Outcomes of interest to these stakeholders include traditional clinical events such as hospitalizations, emergency room visits, and mortality as well as patientcentered outcomes of growing interest, such as symptoms, treatment preferences, quality of life, and satisfaction with care.…”
Section: Potential Benefits Of Pct Designs In Ckdmentioning
confidence: 99%
“…However, extended follow-up analysis of this trial found that nurse practitioner support decreased risk of a combined renal outcome (doubling of creatinine, ESRD or death) by 20 % [24]. Recently, a randomized pragmatic trial of 2199 veterans found that a telephone-based pharmacist intervention improved CKD-related lab testing and increased the number of antihypertensive medications prescribed, but had no significant effect on blood pressure [25]. However, pharmacists in this study were limited to one-time telephone contacts with patients and could only recommend medication changes to primary care providers.…”
Section: Discussionmentioning
confidence: 99%